2010
DOI: 10.3324/haematol.2010.031336
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CEBPA mutations and promoter hypermethylation in pediatric acute myeloid leukemia

Abstract: The online version of this article has a Supplementary Appendx. BackgroundDysfunctioning of CCAAT/enhancer binding protein α (C/EBPα) in acute myeloid leukemia can be caused, amongst others, by mutations in the encoding gene (CEBPA) and by promoter hypermethylation. CEBPA-mutated acute myeloid leukemia is associated with a favorable outcome, but this may be restricted to the case of double mutations in CEBPA in adult acute myeloid leukemia. In pediatric acute myeloid leukemia, data on the impact of these mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 42 publications
5
62
2
1
Order By: Relevance
“…Non-DS pediatric NK AML cases are characterized by various abnormalities, including overexpression of specific genes (MN1, BAALC, and ERG), 29 but also single gene mutations such as FLT3-ITD, WT1, NPM1, and CEBPA, [30][31][32] as well as cryptic translocations. 33 We recently showed that the abnormalities mentioned above are absent or rare in (NK-) ML-DS.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Non-DS pediatric NK AML cases are characterized by various abnormalities, including overexpression of specific genes (MN1, BAALC, and ERG), 29 but also single gene mutations such as FLT3-ITD, WT1, NPM1, and CEBPA, [30][31][32] as well as cryptic translocations. 33 We recently showed that the abnormalities mentioned above are absent or rare in (NK-) ML-DS.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…The independence of prognostic factors was examined by multivariate Cox regression analysis, including in pediatric AML-established prognostic factors such as age, WBC count at diagnosis, favorable karyotype, NPM1 mutation, CEBPA double mutation (CEBPA-DM), and FLT3-ITD. 45 Age and WBC count were included as continuous variables. Favorable karyotype was defined as patients harboring t(15;17)(q21;q22), inv(16)(p13q22), or t(8;21)(q22;q22).…”
Section: Gata2 As Prognostic Marker In Pediatric Aml 2067mentioning
confidence: 99%
“…Type 1 abnormalities mainly induce proliferation, and consist for instance of mutations in tyrosine kinase receptors such as the FLT3-gene (Zwaan, et al 2003a) or KITmutations (Goemans, et al 2005, Pollard, et al 2010, and type 2 abnormalities induce maturation arrest and mainly result from genetic aberrations in hematopoietic transcription factors, either resulting from translocations, or from mutations in genes such as NPM1, GATA1 and CEBPA. (Ahmed, et al 2004, Hollink, et al 2011, Hollink, et al 2009c Evidence for this model is supported by several factors: 1) AML-specific translocations can already be demonstrated in cord-blood (Wiemels, et al 2002), and may only cause AML several years later, 2) fusion transcripts may be demonstrated using sensitive techniques in patients in long-term clinical remission of AML (Leroy, et al 2005), 3) FLT3 mutations induce a myeloproliferative disorder in mice but lack the maturation arrest typical of full-blown AML (Kelly, et al 2002b), and 4) certain type I and II genetic aberrations cluster together in a non-random fashion. Conventional karyotyping may identify AML-specific abnormalities, which are not only of use in diagnosis and the correct classification of the leukemia, but may also provide prognostic information used for risk-group stratification of pediatric AML.…”
Section: Cytogenetics and Molecular Genetic Screeningmentioning
confidence: 99%
“…(Balgobind, et al 2011a, Marcucci, et al 2011 NPM1 and CEBPA gene mutations confer good clinical outcome, whereas mutations in the FLT3 and WT1-genes confer poor clinical outcome. (Ho, et al 2009, Ho, et al 2010b, Hollink, et al 2011, Hollink, et al 2009a, Hollink, et al 2009c, Zwaan, et al 2003a Figure 2 shows the distribution of type 1 and 2 abnormalities, as identified in >400 cases of pediatric AML. We have arbitrarily included the WT1 mutations as type I aberrations, however, their role in AML still has to be elucidated.…”
Section: Cytogenetics and Molecular Genetic Screeningmentioning
confidence: 99%
See 1 more Smart Citation